2005
DOI: 10.1097/01.wnr.0000174407.09515.cc
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala reactivity to emotional faces predicts improvement in major depression

Abstract: Behavioral studies suggest that emotional reactivity in depressed persons predicts subsequent symptom reduction. Using functional magnetic resonance imaging in a prospective study, we show that greater amygdala activation to emotional facial expressions among depressed patients predicts symptom reduction 8 months later, controlling for initial depression severity and medication status. Functional magnetic resonance imaging may thus be used as a method to identify neural markers in depressed patients at risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 22 publications
7
105
3
Order By: Relevance
“…Unlike some studies that found increased or prolonged activation in the amygdala to emotional stimuli (Sheline et al, 2001, Siegle et al, 2002, Fu et al, 2004, Canli et al, 2005, Siegle et al, 2006, we did not find a significant change in amygdala activation in our MDD patients relative to controls. However, we found an increase in activation to sad vs. neutral distractors in the cortex surrounding the amygdala (i.e., in the uncus), IFG (BA 47) and hypothalamus at a reduced threshold, suggesting a hyperactivated emotional system in MDD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike some studies that found increased or prolonged activation in the amygdala to emotional stimuli (Sheline et al, 2001, Siegle et al, 2002, Fu et al, 2004, Canli et al, 2005, Siegle et al, 2006, we did not find a significant change in amygdala activation in our MDD patients relative to controls. However, we found an increase in activation to sad vs. neutral distractors in the cortex surrounding the amygdala (i.e., in the uncus), IFG (BA 47) and hypothalamus at a reduced threshold, suggesting a hyperactivated emotional system in MDD.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike other studies that reported significantly stronger activation to negative emotional stimuli in the emotional system in MDD (Sheline et al, 2001, Siegle et al, 2002, Fu et al, 2004, Canli et al, 2005, Siegle et al, 2006, the MDD group only showed increased activation than the control group using a less stringent statistical threshold (p < .05 uncorrected, spatial extent of 5 voxels) in the emotional system including the left IFG (BA 47), hypothalamus, inferior temporal gyrus as well as right uncus, ventral basal ganglia, and ventral extrastriate cortex. We further investigated whether antidepressant medication weakened the activation to emotional stimuli in the MDD group.…”
Section: Fmri Resultscontrasting
confidence: 80%
“…The present study in subjects reporting high levels of anxiety complements previous studies in subjects with depression showing that neural responsivity in the rACC (36,37) and amygdala (38) can predict drug treatment outcomes (18,39). Here we show that inverse rACC-amygdala activity can predict changes in reported anxiety as measured by the HAM-A in adult subjects with GAD who were specifically recruited because of their low levels of depressive symptoms and lack of comorbid diagnosis.…”
Section: Discussionsupporting
confidence: 52%
“…Impaired perception of sadness, rejection, or anger was associated with a less favorable course of depression (Bouhuys et al, 1996) and poor perception of negative emotions in faces was associated with relapse (Bouhuys et al, 1999). In a functional neuroimaging study by Canli et al (2005), amygdala reactivity to emotional faces predicted improvement of clinical symptoms. These findings suggest that inappropriate reactions may be linked to maintenance or exacerbation of depression.…”
Section: Introductionmentioning
confidence: 99%